2005
DOI: 10.1631/jzus.2005.b1069
|View full text |Cite
|
Sign up to set email alerts
|

Protein and hordein fraction content in barley seeds as affected by sowing date and their relations to malting quality

Abstract: The effect of sowing date on grain protein, hordein fraction content and malting quality of two-rowed spring barley was investigated by using ten commercial cultivars with different grain protein content and the relationships among these traits were examined. The results showed that grain protein content and B hordein content increased as the sowing date postponed and were significantly affected by sowing date, while C and D hordein contents were less influenced by sowing date. There were significant differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 33 publications
4
34
0
2
Order By: Relevance
“…Although those accesses were elite genotypes, they indicated a wide variation in the protein content, presenting a value up to 14.13% (C-70). The genotype -environment interaction might explain the fact that an access, like cultivar BRS 180, ended up showing variability in its protein content (Molina-Cano et al, 1997;Qi et al, 2005;Yalçin et al, 2007). In an irrigated system in the Brazilian savannah, Amabile et al (2008) observed a great variability regarding the protein content within the same year or in different years.…”
Section: Resultsmentioning
confidence: 99%
“…Although those accesses were elite genotypes, they indicated a wide variation in the protein content, presenting a value up to 14.13% (C-70). The genotype -environment interaction might explain the fact that an access, like cultivar BRS 180, ended up showing variability in its protein content (Molina-Cano et al, 1997;Qi et al, 2005;Yalçin et al, 2007). In an irrigated system in the Brazilian savannah, Amabile et al (2008) observed a great variability regarding the protein content within the same year or in different years.…”
Section: Resultsmentioning
confidence: 99%
“…The smallest protein contents for straw (1.84% and 1.64%) and grain (5.4% and 4.9%) were achieved in the first and second year, respectively by full irrigation method due to early time of sowing at 23 October. The results of the study carried out by Qi et al (2005) indicated that grain protein content increased as the sowing date was postponed and it was significantly affected by the sowing date. In their research sowing date in 26 March had smallest, while sowing date in 25 April had the highest largest, content of protein in the barley grain.…”
Section: Grain and Straw Protein Contentmentioning
confidence: 99%
“…In barley, proteins are related to malting quality by their multiple roles in yeast nutrition, in haze formation in beer (See et al, 2002), in foam stability (Roberts et al, 2003), in enzyme activities (Clancy et al, 2003;Hayes et al, 2003) and in PAGE protein profile related to endosperm structure (Qi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%